FAKTOR-FAKTOR PENDORONG DAN PENARIK CALON MAHASISWA MEMILIH JASA PENDIDIKAN TINGGI: STUDI KILAS BALIK - Grace Putlia; John J.O.I. Ihalauw (Journal of Business & Applied Management, 2016)
This retrospect study aims at studying the push and pull factors of prospective students in choosinghigher education services of the management program of study at Satya Wacana Christian University.This retrospect study uses grounded theory design with triangulation of data sources. The findingsshowed three push factors, namely suitable benefit offered, prospect‟s motivation, and trustedrecommendation. Twelve pull factors include service availability, promotion-mix, location, servicequality, relationship, reputation, communication, process, price, human resources, facility, andguarantee. A mini-theory comprising of a set of 17 propositions is proposed to be further tested infuture.Keywords: push factor, pull factor, mini-theory